Glycogen Synthase Kinase-3 Regulates Sperm Motility and Acrosome Reaction via Affecting Energy Metabolism in Goats - Zhu, Zhendong; Li, Rongnan; Wang, Liqiang; Zheng, Yi; Hoque, S. A. Masudul; Lv, Yinghua; Zeng, Wenxian (Frontiers in Physiology, 2019)
Hyperactivation and acrosome reaction of sperm are pre-requisite steps for fertilization. However, the hyperactivation and acrosome reaction are critically controlled through the phosphorylation of specific proteins. Glycogen synthase kinase-3 (GSK3), a serine/threonine kinase with two different isoforms (α and β), is involved in biochemical signaling pathways. This study was aimed to investigate whether the GSK3α/β is present in goat sperm and its regulatory role in sperm motility and acrosome reaction. GSK3α/β was detected with immunofluorescence and Western blotting. Sperm motility, membrane integrity, acrosome reaction, mitochondrial membrane potential, phospho-Ser21-GSK3α and phospho-Ser9-GSK3β were analysed. The ATP production and activities of lactate dehydrogenase (LDH), malate dehydrogenase (MDH) and succinate dehydrogenase (SDH) were measured. It was observed that the GSK3α/β was expressed in goat sperm, especially in the peri-acrosomal, mid-piece and principal piece of the tail. The abundance of GSK3α/β in sperm was increased during transit along the epididymis. Addition of either 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) or CHIR99021 significantly increased the sperm motility patterns and GSK3α/β phosphorylation. Interestingly, the adenosine triphosphate (ATP) production, activities of LDH, MDH and SDH were observed to be increased in the CHIR99021 treatment. The results suggested that GSK3α/β regulates sperm motility and acrosome reaction via phospho-ser21-GSK3α and phospho-ser9-GSK3β that involved in the regulation of sperm energy metabolism.